2016
DOI: 10.1111/ene.13130
|View full text |Cite
|
Sign up to set email alerts
|

Health‐related quality‐of‐life outcome in patients with idiopathic normal‐pressure hydrocephalus – a 1‐year follow‐up study

Abstract: Less than half of the patients with iNPH experienced clinically significant favorable HRQoL outcome, partly explained by the patient's characteristics and comorbidities. The HRQoL approach reveals aspects that are important for the patient's well-being, but may also improve the quality of the outcome assessment of cerebrospinal fluid shunting. Study results may help clinicians to estimate which patients will benefit shunt surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
49
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(49 citation statements)
references
References 34 publications
0
49
0
Order By: Relevance
“…The intent of current literature is to decrease complications and their consequences. The technology of shunt, its materials and the surgical techniques may decrease mechanical and infectious complications [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The intent of current literature is to decrease complications and their consequences. The technology of shunt, its materials and the surgical techniques may decrease mechanical and infectious complications [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] .…”
Section: Discussionmentioning
confidence: 99%
“…Overdrainage can lead to slit-ventricle syndrome, which is characterized by small or slit-like ventricles, coupled with transient episodes of symptoms of raised ICP. Changes in shunt, designed to address the problem of overdrainage, include valves designed to open at different pressures and selected based upon the patient's characteristics; anti-siphoning devices to minimize the siphon effect caused by changes in posture; and valves that regulate by flow rather than by pressure differences [13][14][15][16][17][18][19] .…”
Section: Discussionmentioning
confidence: 99%
“…4 In contrast, PROs, such as Health-Related Quality of Life (HRQoL), may appreciate aspects not captured by ClinROs. [5][6][7][8][9] Recently, we published a prospective 1-year follow-up study of HRQoL outcome in patients with idiopathic normal-pressure hydrocephalus (iNPH), 9 a progressing condition of elderly patients that characteristically impairs their gait, cognition, and urinary continence. [10][11][12] The so-far unknown origin has been contemplated to cause various abnormalities in the cerebrospinal fluid (CSF) physiology and hydrodynamics, which ultimately lead to the symptoms and signs observed in patients with iNPH.…”
Section: Introductionmentioning
confidence: 99%
“…7,8 Despite of 2 decades of research, investigators have found very little common ground in choosing a HRQoL instrument for patients with dementia, determining the optimal way of administrating it, and deciding what dimensions and qualities it should or should not have. 7,8,14,15 Only little is known about HRQoL in iNPH, 9 and there are no guidelines for the measurement of HRQoL in iNPH.…”
Section: Introductionmentioning
confidence: 99%
“…New strategies to improve service provision with accelerated diagnosis and treatment are being employed, e.g., through telemedicine , a model that appears successful. Neurological involvement in medicine remains active across a large spectrum of presentations . Novel mutations in adult‐onset leukoencephalopathy and the spinocerebellar ataxias and the search for biomarkers in neurological disease are some examples of the involvement of neurology research across this spectrum.…”
mentioning
confidence: 99%